High non-relapse mortality and low relapse incidence in gender-mismatched allogeneic hematopoietic stem cell transplantation from a parous female donor with a male child. Issue 3 (4th March 2017) - Shinohara, Akihito; Inamoto, Yoshihiro; Kurosawa, Saiko; Hiramoto, Nobuhiro; Ueda, Ryosuke; Tanaka, Takashi; Tada, Kohei; Kobayashi, Yujin; Morikawa, Noriyuki; Okinaka, Keiji; Kim, Sung-Won; Tajima, Kinuko; et al.
Abstract: To clarify the influence of exposure to a male fetus during a female donor's (FD) pregnancy in allogeneic hematopoietic stem cell transplantation (HSCT), we retrospectively examined 292 HSCT patients. The 5-year non-relapse mortality (NRM) was 33.5% among 31 male recipients who had HSCT from FD with a male child (MC), 23.0% among 40 male recipients who had HSCT from FD without MC and 19.6% among 221 other recipients. The 5-year relapse incidence (RI) was 22.6%, 42.0%, and 43.1% for the respective group. In multivariate analysis, male recipients who had HSCT from FD with MC had an increased risk of NRM (hazard ratio [HR] 1.92, 95% CI 1.08–3.42, p  = .03), a reduced risk of RI (HR 0.42, 95% CI 0.18–0.96, p  = .04), resulting in no significant difference regarding overall survival. Male child of FD is suggested to influence NRM and RI in gender-mismatched HSCT.